Ehrlichia chaffeensis Infection of Sika Deer, Japan - Makoto Kawahara; Tomoko Tajima; Harumi Torii; Mitsutaka Yabutani; Joji Ishii; Makiko Harasawa; Emiko Isogai; Yasuko Rikihisa (Emerging Infectious Diseases, 2009)
To determine whether Ehrlichia chaffeensis exists in Japan, we used PCR to examine blood from sika deer in Nara, Japan. Of 117 deer, 36 (31%) were infected with E. chaffeensis. The E. chaffeensis 16S rRNA base and GroEL amino acid sequences from Japan were most closely related to those of E. chaffeensis Arkansas.